2021
DOI: 10.1002/bmc.5127
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the essential oil content and composition of Salvia limbata C.A. Mey at different growth stages and altitudes

Abstract: BackgroundThe present study investigates the effect of growth stage (vegetative, owering and seed ripening) and altitude (1500, 2000 and 2500 m above sea level) on the content and chemical composition of S. limbata essential oil which belongs to Lamiaceae family. ResultsAccording to the oil analysis, 28 components representing 96.5% to 99.7% of the total volatile oil composition were characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The contents of the components in plants are affected by their variety, place of origin, growth environment, processing methods, etc. [106][107][108][109]. Some factors relevant to the content of curcumenol (e.g., the constituents of minerals in the soil and the harvest season of herbs) have been illustrated.…”
Section: Other Factors Influencing the Content Of Curcumenolmentioning
confidence: 99%
“…The contents of the components in plants are affected by their variety, place of origin, growth environment, processing methods, etc. [106][107][108][109]. Some factors relevant to the content of curcumenol (e.g., the constituents of minerals in the soil and the harvest season of herbs) have been illustrated.…”
Section: Other Factors Influencing the Content Of Curcumenolmentioning
confidence: 99%
“…Numerous studies have examined the physical factors of the landscape in different dimensions. For example, research has shown the impact of different ecological stresses on seed germination in protected areas (Saffariha et al, 2020), and different altitudes affect the essential oil content and plant composition (Saffariha et al, 2021). Moreover, for a comprehensive under- standing of the human perception of landscape, one needs to assess how individual elements (not only the overall landscape) located in the landscape are perceived (Kaplan and Kaplan, 1989;Rogge et al, 2007).…”
Section: Landscape Characteristicmentioning
confidence: 99%
“…All over the world, on the one hand with the increase in the prevalence of cancer, cardiovascular diseases, Alzheimer’s, etc., and on the other hand, the increase in use of the internet and the media, interest in healthy nutrition and therefore antioxidant and anticancer compounds and functional foods has increased (Ertas, Cakirca, et al, 2021; Ertas, Fırat, et al, 2021; Mohammadhosseini et al, 2021). For these reasons, interest in natural products for use to prevent cancer and aging‐related ailments is increasing (Mohammadhosseini, 2017; Saffariha et al, 2021). For these reasons, it is important to determine in which species and families compounds with bioactive potential are found and in what quantities.…”
Section: Introductionmentioning
confidence: 99%